Sámi Healthcare Staff Experiences of Encounters with Sámi Patients and Their Expectations for Non-Sámi Healthcare Staff - Tove Mentsen Ness; Grete Mehus (Nursing Reports)
Objective: The aim of this study was to explore Sámi healthcare staff experiences in encounters with Sámi patients and their expectations for non-Sámi healthcare staff. Methods: Focus groups and individual interviews with 14 participants were conducted, and the participants’ experiences were subjected to a thematic analysis approach. Results: The findings show that the Sámi healthcare staff expect non-Sámi healthcare staff to enhance their knowledge about Sámi language and culture. The Sámi healthcare staff also expect non-Sámi healthcare staff to gain knowledge of diversities within the Sámi cultures. Additionally, the results show that the participants felt that the encounters were more authentic when the patients had the same background as themselves. Conclusion: These results were also based on the participants’ experience of resistance from non-Sámi healthcare staff, which can be addressed by the non-Sámi healthcare staff and healthcare institutions enhancing their knowledge of Sámi history, culture, and language. This can be conducted by making efforts to meet the participants’ expectations and experiences, enhancing their knowledge of Sámi history, culture, and language, and showing respect to provide culturally safe care. Further, tacit knowledge and what can be seen as “two-eyed seeing”, as demonstrated by the participants, are not necessarily transferable to non-Sámi healthcare staff. Despite this, all healthcare staff, through experience, recognition, and reflections on encounters with Sámi patients and Sámi healthcare staff, can develop awareness in what is addressed as “two-eyed seeing” by the participants in this study.